Programming mRNA decay to modulate synthetic circuit resource allocation - Ophelia S. Venturelli (Nature Portfolio, 2017)
Synthetic circuits in host cells compete with endogenous processes for limited resources. Here the authors use MazF to funnel cellular resources to a synthetic circuit to increase product production and demonstrate how resource allocation can be manipulated.